P465 Is golimumab serum level predictive of clinical remission after intensification for loss of response in patients with ulcerative colitis?. (21st January 2022) - Fumery, M; Nancey, S; Filippi, J; Altwegg, R; Hebuterne, X; Boschetti, G; Veyrard, P; Yzet, C; Paul, S; Roblin, X
Abstract: Background: Loss of response to golimumab occurs in nearly 40% of patients with ulcerative colitis (UC). Unlike others anti-TNF, no study has reported a correlation between serum golimumab level and response to drug intensification. The objective of this study was therefore to determine a threshold of serum golimumab before intensification predictive of clinical remission after optimization. Methods: We included consecutive patients with UC and loss of response to golimumab (Mayo score between 6 and 12 and an endoscopic Mayo sub-score> 1) in a prospective multicentric cohort. Patients with loss of response at 50 mg / 4 weeks (W) and 100 mg / 4W underwent therapeutic intensification at 100 mg / 4W and 100 mg / 2W, respectively. Patients were followed prospectively with a first evaluation between weeks 2 and 4 (visit 2) and between weeks 4 and 8 (visit 3) after intensification. Clinical remission was defined by partial Mayo score ≤ 1. Serum level and anti-golimumab antibodies were evaluated at each visit (Lisa Tracker, Theradiag France). Results: A total of 47 patients (female, 50%; median age, 39 years (IQR, 27–52) treated with golimumab for a median of 20.4 weeks (IQR, 10.7–38.3) were included. The median partial Mayo score was 6 (IQR, 5–7) and the endoscopic Mayo score was 3 (IQR, 2–3). The median golimumab serum level before intensification was 2.23 µg / mL (IQR, 1.02–3.96) and only three patients (6.2%) had anti-drug antibodies. After a total of 50 drug intensification, 23 (48.9%) patients had clinical response (100 mg / 4W: 14/25 (58.3%); 100 mg / 2W: 9/25 (36%)), 10 (21%) clinical remission and 18 (39%) endoscopic response. The median golimumab levels before intensification were respectively 2.17 µg / mL (IQR, 0.97–3.25) and 2.47 (IQR, 1.10–4.05) in responders and non-responders (p = 0.66), and 1.11 µg / mL (IQR, 0.59–2.29) and 2.47 µg / mL (IQR, 1.21–3.83) in patients with and without clinical remission after intensification (p = 0.054). In multivariate analysis, intensification to golimumab 100 mg / 2W ( vs 100 mg / 4W) (OR, 0.11 [95%CI, 0.01 - 0.87], p=0.037) and change of golimumab level between V1 and V2 (OR, 1.48 [95%CI, 1.02 - 2.14], p=0.037) were significantly associated with clinical remission after intensification. Only one serious adverse event (infection) was reported during the 24-week follow-up. Conclusion: In this prospective multicentric study, half of patients recaptured response following golimumab intensification in UC. Change of golimumab level was predictive of clinical remission after intensification.